1995
DOI: 10.1128/mcb.15.12.6961
|View full text |Cite
|
Sign up to set email alerts
|

An Immunological Renal Disease in Transgenic Mice That Overexpress Fli-1, a Member of the ets Family of Transcription Factor Genes

Abstract: The proto-oncogene Fli-1 is a member of the ets family of transcription factor genes. Its high expression in the thymus and spleen and the presence of DNA binding sites for Fli-1 in a number of lymphoid cell-specific genes suggest that Fli-1 is involved in the regulation of lymphopoiesis. Activation of the Fli-1 gene by either chromosomal translocation or viral insertion leads to Ewing's sarcoma in humans and erythroleukemia in mice, respectively. Thus, Fli-1 is normally involved in pathways involved in the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
106
0
2

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(112 citation statements)
references
References 32 publications
4
106
0
2
Order By: Relevance
“…Over-expression of Fli1 in otherwise healthy mice results in an abnormal expansion of autoreactive lymphocytes, production of autoantibodies and the development of an autoimmune kidney disease similar to that observed in murine models of lupus (Zhang et al, 1995). Subsequently, it was observed that Fli1 is over-expressed in the lymphocytes of lupus prone mouse models MRL/lpr and NZB/NZW f1 (Georgiou, 1996;Zhang et al, 2004) and in PBMCs from human lupus patients (Georgiou, 1996).…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations
“…Over-expression of Fli1 in otherwise healthy mice results in an abnormal expansion of autoreactive lymphocytes, production of autoantibodies and the development of an autoimmune kidney disease similar to that observed in murine models of lupus (Zhang et al, 1995). Subsequently, it was observed that Fli1 is over-expressed in the lymphocytes of lupus prone mouse models MRL/lpr and NZB/NZW f1 (Georgiou, 1996;Zhang et al, 2004) and in PBMCs from human lupus patients (Georgiou, 1996).…”
Section: Introductionmentioning
confidence: 72%
“…However, the induction of lupus by increasing Fli1 levels in non-autoimmune prone mice (Zhang et al, 1995) and reduction of disease by reducing Fli1 levels in lupus prone mice (Zhang et al, 2004) indicate strongly that the immune system and lupus disease progression are sensitive to the levels of Fli1. Gaining a better understanding of how Fli1 gene expression is controlled normally will be critical for determining how it becomes dysregulated in lupus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have tested extensively the possibility that the nephrotic syndrome in Em-pp-Frat1 transgenic mice is caused by a systemic autoimmune disease, but we have thus far obtained no evidence for this notion. Em-pp-Frat1 animals do not display the accumulation of immune deposits in the kidney, nor do they show the hypergammaglobinemia, splenomegaly, and selfreactive T and B cell populations as observed in lupus nephritis or Fli1-induced renal disease (Zhang et al, 1995;Kotzin, 1996). Moreover, the responses of Empp-Frat1 thymocytes to various apoptotic stimuli (including a-Fas), and the apoptotic response of activated peripheral T cells to IL-2 withdrawal were found to be normal.…”
Section: Nephrotic Syndrome In Frat1 Transgenic Micementioning
confidence: 95%